Complications and implications of Caesarean delivery: Facts and perceptions - Javeed A. Golandaj; Mallikarjun S. Kampli; Manish Kumar; Jyoti S. Hallad (Elsevier, 2024)
Background/objectives: Caesarean delivery (CD), though considered a life-saving surgical procedure, poses a public health problem and puts mothers and babies at higher risk of post-delivery complications. The present study aims to explore the post-delivery maternal complications among CD and normal vaginal delivery (NVD) mothers in India. Methods: The present study is a PAN-India study conducted across various Indian states, considering a significant increase in CD rates. Data was collected from face-to-face interviews of 1407 recently delivered mothers during January-March 2023. Results: The findings indicate that 22 % of CD mothers reported post-delivery complications compared to 15 % of NVD mothers. Notable complications among CD mothers include body/abdominal pain (12.9 %), infection/pain in the suture area (6.2 %), and high blood pressure (1.1 %). Conversely, higher proportion of NVD mothers reported pelvic pain (3.3 %). Further, a greater proportion of NVD (22 %) and CD (28 %) mothers reported pain in the pelvic area and infection/pain in the suture area, respectively. Socio-economic and demographic factors such as age, education, and residence significantly influenced the incidence of self-reported maternal complications. Mothers aged 25 and above, with at least ten years of education, and those residing in urban areas reported higher complications. Additionally, CD mothers also experienced longer hospital stays, higher costs, and delays in breastfeeding initiation. Conclusion: The study underscores the necessity for targeted healthcare interventions to mitigate the specific risks associated with CDs and improve maternal outcomes through appropriate policy formation to address the rising trend of CDs and their implications on maternal health.